The Fire on the Körönd By The Eyes of an Engineer Part. III. The Second Time of Averting of Life-Danger, Preparation on Conservation - Lámer, Géza (International Journal of Engineering and Management Sciences, 2016)
The roof and the closing floor of the building located Andrássy Street 83-85. damaged by the fire on the Körönd. We describe the damages caused by fire, and present the state of the building after damage caused by fire.